Integrating Positive Psychology through ESP Learning for Science Classes in Senior High School - Selvia Ruyatus Saefullah; Iin Indra Nuraeni; Reni Marlina; Endang Komara; Nandang Koswara (Postgraduate, University of Mataram, 2023)
This research aims to identify positive psychology through ESP learning in science classes at senior high schools in Indonesia. This study used qualitative method. The data collection method employed interviews and observations to obtain more detailed information regarding the research findings. Three distinct data collection methods involved observation, interview, and questionnaire. The qualitative data analysis method was from data summarization, data presentation, and drawing conclusions. Research instruments used triangulation, which involved interviews, observations, and documentation. Based on the findings, it can be concluded that positive psychology serves as a connection or link between humanism and transpersonal. The concept of developing personality potential is evident in Positive Psychology, which also incorporates transcendence as one of its virtues, particularly in relation to spirituality and meaningfulness. The ESP learning concept can enable students to actively participate in foreign language teaching practices in the natural science learning process.